Cooking the Mexican way - Coronado, Rosa (Lerner Publications Company Minneapolis, 1982)
Introduces fundamentals of Mexican cooking, including special ingredients and cooking utensils. Also provides recipes for suggested dishes
Includes index.
10 - 12 years
Keywords: Cokery, Mexican -- Juvenile literature; Mexico -- Juvenile literature; Cookery, Mexico; Mexico -- Social life and customs